Cardiometabolic risk in children and adolescents with obesity: a position paper of the Italian Society for Pediatric Endocrinology and Diabetology - Giuliana Valerio; Procolo Di Bonito; Valeria Calcaterra; Valentino Cherubini; Domenico Corica; Luisa De Sanctis; Anna Di Sessa; Maria Felicia Faienza; Elena Fornari; Lorenzo Iughetti; Maria Rosaria Licenziati; Melania Manco; et al. (BMC, 2024)
Abstract Despite the implementation of preventive measures to counteract the obesity epidemics, the prevalence of childhood obesity is still alarming all over the world. Childhood obesity is the most common risk factor for both cardiovascular and metabolic diseases. In fact, an earlier onset of obesity can cause a greater risk of adiposity tracking across the lifespan and consequently a longer exposure to cardiometabolic risk factors. Accumulating evidence provided by prospective and intervention studies demonstrated the link between pediatric obesity and selected subclinical signs of cardiovascular damage (atherosclerosis and left ventricular hypertrophy), or fatal and not fatal cardiovascular events as early as 40 years of age. The numerous guidelines and scientific documents published in the last years demonstrate the relevance of assessing cardiometabolic risk factors in children and adolescents with OB. This Position paper, released by experts of the "Childhood Obesity study group" within the Italian Society for Pediatric Endocrinology and Diabetology, aims to review the assessment of cardiometabolic risk factors and comorbidities in children and adolescents with OW/OB on the light of the most recent scientific evidence. The main recommendations are: (a) early detection of comorbidities, including hypertension, dyslipidemia, prediabetes/type 2 diabetes, metabolic dysfunction-associated steatotic liver disease, polycystic ovary syndrome, inactivity, obstructive sleep apnea and decline in kidney function; (b) weight loss treatment, which is associated with a reduction of all cardiometabolic risk factors; (c) specific treatment of comorbidities, through lifestyle modifications or pharmacological treatment added to lifestyle for suitable individuals; d). monitoring comorbidities for mitigating future morbidity and mortality.